Comparison of Psychological Distress and Mental Health Literacy Levels of Hospitalized COVID-19 Patients, Individuals under Quarantine, and Healthy Individuals of Society in The Pandemic - AkgÃ¼n, Åženay (Universitas Negeri Padang)
Aim: This study aimed to find out which group is most affected by psychological distress during the pandemic and determination of MHL level.Methods: This is cross a sectional study. Research sample consisted of 814 voluntary people. The study used descriptive data form, Kessler psychological distress scale and mental health literacy scale. Before the study was conducted, permission was obtained from necessary institutions and then research ethics committee approval was obtained. Also, individuals who were contacted through online platforms were informed about the study and provided informed consent forms by clicking â€œyesâ€ option which showed their voluntary participation. The data were analyzed using descriptive statistics, t-test, analysis of variance, and Mann Whitney U and Kruskal Wallis tests. To detect correlations, the correlation and regression analyses were used.Results: The study results showed that 28% of the participants had diagnosable psychological distress (30-50) and individuals who received COVID-19 treatment at hospital had the highest median score (30). The mental health literacy of the participants was low (106) and the lowest scores belonged to individuals under treatment of COVID-19 at hospital. The highest psychological distress was in the Black Sea region and the lowest mental health literacy was in Southeastern Anatolia region. There was a significant very weak positive correlation between psychological distress scale and mental health literacy.Conclusion: Individuals who had COVID-19 disease had high psychological distress and low mental health literacy. After the pandemic, the community should be screened for mental illnesses and mental health literacy training should be organized to improve mental health. Nurses need to use their collaborative and advocacy roles regarding mental evaluation, providing consultancy and treatment during nursing care to patients with COVID-19.